KOMUNIKASI ORGANISASI SUPORTER SEPAK BOLA THE JAKMANIA RUNYEM BOYS DENGAN MASYARAKAT DI WILAYAH JAKARTA UTARA - Muhammad Ilyas; Christoper Yudha Erlangga (Tamilis Synex: Multidimensional Collaboration, 2025)
This study aims to answer the formulation of the problem of how the organizational communication pattern of The Jakmania supporter group in North Jakarta with the community and its influence on social relations in the environment. Using a qualitative descriptive approach and symbolic social interaction theory, this study explores the horizontal communication pattern applied in this community. The inclusive and equal communication pattern between the leader and members allows for the creation of various positive activities, such as social services, fundraising, and education for the community. This open communication not only strengthens the internal solidarity of the community but also strengthens external relations with the surrounding community. However, the study also found that excessive fanaticism among members can be a challenge, especially when it triggers conflict with other supporter groups. The results of the study confirm that effective organizational communication is the main key to maintaining harmony between the supporter community and the community. This study makes an important contribution to understanding the dynamics of organizational communication in the supporter community and its role in building productive, peaceful, and inclusive social interactions